The value of folate receptor-positive circulating tumour cells as a diagnostic biomarker for lung cancer: a systematic review and meta-analysis - Fangjun Chen; Yihong Ni; Jin Zhang; Yang Hao; Zhoujunyi Tian; Guangliang Qiang (Journal of International Medical Research, 2023)
Objective To conduct a systematic review and meta-analysis evaluating the diagnostic value of folate receptor-positive (FR+) circulating tumour cells (CTCs) as a potential tumour marker for lung cancer diagnosis. Methods The PubMed, Embase, and Web of Science databases were searched for relevant articles published between database inception and November 2022. Eligible studies were selected based on inclusion and exclusion criteria. Sensitivity, specificity, positive and negative likelihood ratios, diagnostic odds ratio, and area under the curve (AUC) were pooled with 95% confidence intervals (CI), using RevMan 5.4 and STATA 17.0 software to assess the diagnostic value of FR+CTC for lung cancer. Results After screening, 11 studies involving 3469 subjects were eligible for inclusion. The pooled sensitivity and specificity were 0.79 (95% CI 0.76, 0.82) and 0.84 (95% CI 0.81, 0.96), respectively, and the pooled positive and negative likelihood ratios were 4.90 (95% CI 4.25, 5.65) and 0.25 (95% CI 0.22, 0.29), respectively. The pooled diagnostic odds ratio was 19.70 (95% CI 16.06, 24.16). The AUC of the pooled summary receiver operating characteristic curve was 0.89 (95% CI 0.85, 0.91). Sensitivity analysis showed that this result was stable after one-by-one study elimination. Conclusion Folate receptor-positive CTCs may have good diagnostic value in lung cancer.